الإشكالیة في الحدیث “إن الله خلق آدم على صورتھ”: أسبابھا وحلولھا - Angraini binti Ramli (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2018)
Hadith Innallāha khalaqa Adam ‘alā ṣūratih, is one of hadith that has isykāl (difficulties) or problems involving debates among scholars. Firstly, There are some scholars who argued that the problems in this hadith is because the pronunciation of ‘alā ṣūratih in this hadith is contrary to the Islamic faith. Secondly, Others argued that this hadith has a similarity with isrā’iliyāt because in the Torah and the Gospel also found similar things in the creation of Adam. Thirdly, some scholars accept this hadith textually but interpreted it to another meaning in order fit with holiness of Allah. The fourth,opinion argue that damiror pronoun of words on ‘alā ṣūratih refer to Allah, either as interpretation the word of rahman or as an iḍāfah taṣrīfiyah and ikhtiṣāṣiyah to Allah. The fifth, opinion argue that this damir refer to Adam. The sixth, opinion said that this damir returned to the owner face who was beaten as mentioned in the hadith is refer to the object which was hit, namely the face itself